Propofol or Midazolam for Sedation and Early Extubation Following Coronary Artery Bypass Graft Surgery - Shumaila Ali Rai, Muhammad Imran Khan, Aamer Mahmood Malak, Muhammad Tamseel Asghar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the efficacy of midazolam and propofol for postoperative sedation and early extubation following cardiac surgery. Methods: This randomized control trial was conducted at the Cardiac Surgery Department of the Choudhary Pervaiz Elahi Institute of Cardiology from February 2019 to February 2020. A total of 60 American Society of Anesthesiologists (ASA) III patients planned to undergo coronary artery bypass graft surgery were included. After shifting into intensive care unit (ICU), patients were divided in two groups by lottery method and study drugs propofol and midazolam were started. Both infusions were terminated after four hours and patients were assessed for postoperative sedation and extubation. Hemodynamic parameters, arterial blood gases and respiratory functions were assessed and recorded. Results: The mean time to awakening, time to extubation in midazolam group was 94.11±4.36 minutes, 94.47±6.11 minutes respectively and in propofol group it was 96.58±4.31 minutes, 91.91±3.94 minutes respectively. Difference was statistically significant. Conclusion: Results of our study reveal that there was no difference in both drugs regarding sedation and extubation time, both drugs are safe, effective and useful in patients of coronary artery bypass graft surgery. Keywords: Coronary artery bypass graft, Midazolam, Propofol, Extubation, Sedation.